Hubungan tingkat pengetahuan tentang perawatan payudara dengan kejadian payudara bengkak pada ibu nifas - Sinta Dwi Hapsari Santoso; Yuni Kusmiyati; Margono Margono (Jurnal Kesehatan Ibu dan Anak, 2016)
The incidence of childbirth on breast swelling one contributing factor is the lack of breast care, lack of care of thebreast caused by the lack of a level of knowledge of the mother's breast care about childbirth. The proportion ofincident breast swelling at parturition on maternal health centers Jetis, Yogyakarta city in August-December2010 has increased to 27% of total 119 mothers parturition and 30% of mothers who say never experiencedbreast swelling of 10 respondents encountered and largely due to the lack of knowledge about the care of thebreasts. Research objectives: to know the relationship of the level of knowledge about the care of the breastswith breast swelling at parturition on maternal health centers Jetis, Yogyakarta in 2011. Research methods:observational Analytic with cross sectional approach. Research on location of clinics Jetis, Yogyakarta with asample of 65 mother parturition hospitalization on April 1-May 31, 2011. Data retrieval with the questionnaire.Analysis done with chi square (x 2) with a confidence level of 95%>. The result: a majority of Respondents isprimipara, the level of secondary education, and work. Level of knowledge of the majority of the respondents isthe category less. The majority of respondents experienced swollen breasts. Statistics show chi square p11.3934 or count value 0.003357 means that there is a relationship of the level of knowledge of the care of thebreasts with breast swelling at parturition on maternal health centers Jetis, Yogyakarta. Conclusion: the level ofknowledge about breast carebreast incident-relatedswelling of theparturition in the mother.